(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This research aims to describe the use of capitation funds in improving the quality of services at the Tumpaan Community Health Center, Tumpaan District, South Minahasa Regency. Data collection techniques were carried out by means of observation, interviews and literature study. Based on the results, it can be concluded that the use of capitation funds at the Tumpaan Village Community Health Center has played a role in improving the quality of services. This can be seen from the increase in patient satisfaction with health services at the Tumpaan Village Community Health Center. Patients are satisfied with the services provided by health workers at the Tumpaan Village Health Center. This can be seen from the answers of patients who said that the health services at the Tumpaan Village Community Health Center were good and they were satisfied with the services provided by the health workers at the Tumpaan Village Community Health Center.